Improving the environmental quality of Kesiman Village, Mojokerto Regency through household waste sorting - Fidelis Arastyo Andono; Rizky Eriandani; Dianne Frisko Koan; Esti Dwi Rinawiyanti; Muhammad Wisnu Girindratama (Universitas Muhammadiyah Malang, 2024)
The most significant source of waste in Indonesia is households. This community service aims to improve the environmental quality of Kesiman Village by educating residents to sort waste from their households. This activity begins with observations and interviews with residents. Preliminary survey results show that the waste problem has been around for a long time, and accumulation occurs in the Final Disposal Site (TPA). Based on interviews with villagers, they are willing to participate in the waste management assistance program. Furthermore, waste sorting facilities are provided for each resident's house by empowering village communities with expertise. Counseling or education is carried out at the home of a resident, as well as providing a real example of waste segregation. Sorting is done based on the categories of organic and non-organic waste. Two weeks after the counseling, the service team evaluated by direct surveying several residents' houses to see if the sorting had gone well and smoothly. The evaluation results show that residents understand and carry out waste segregation consistently. However, there are several obstacles; for example, some houses feel the trash can needs to be bigger, and sometimes they place organic and non-organic waste upside down. After the household waste sorting program runs smoothly, the community service team will plan and realize the Village waste management program so that the volume of waste is reduced and the environment is cleaner.